Clinical manifestations, evaluation and management of hyperprolactinemia in adolescent and young girls: a brief review - Matalliotakis, Michail; Koliarakis, Ioannis; Matalliotaki, Charoula; Trivli, Alexandra; Hatzidaki, Eleftheria (Acta Biomedica Atenei Parmensis, 2019)
Hyperprolactinemia (HPrl) is considered as a rare endocrinopathy in childhood. In children and adolescent girls, there are three major categories of HPrl causes; physiological, pathological and iatrogenic. Through hypogonadotropic hypogonadism, prolactin hypersecretion and production leads to the typical functional syndrome which is observed in female children and adolescents; delayed puberty, primary or secondary amenorrhea and/or galactorrhea. Regarding prolactinomas, clinical signs manifest with mass compression of the optic chiasm and anterior pituitary gland or prolactin hypersecretion. Targeted identification of HPrl is of significant importance for proper management and follow-up. The aim of this review is to focus on the evaluation of HPrl in adolescent and young girls. In addition, we aimed to summarize the current knowledge regarding the proper management of such cases.